Decrease of CD68 synovial macrophages in celastrol treated arthritic rats - Cascao, Rita (2022)
Copyright: © 2015 Cascão et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited